Modal Verbs in Textbooks of English for Lower-secondary Learners - Štruncová, Kateřina (Univerzita Pardubice, 2013)
This thesis focuses on the theory connected with central modal verbs and their interpretation in textbooks for lower-secondary learners. The main topic of the paper is the semantic meanings of the modal verbs, their morphological and syntactic characteristics. The paper deals with didactic transformation, its levels and its impact on the presentation of modal verbs in textbooks. The work includes professor Piaget´s conception of the cognitive development of children attending elementary education at Stage 2. The main stress is laid on children´s thinking processes evolving during the stage of formal operations. Finally, the research is conducted so as to examine the outcomes of the modal verbs after the process of the didactic transformation in the textbook.
Prezentace modálních sloves v učebnicích anglického jazyka pro žáky 2. stupně základních škol
Keywords: modální slovesa; didaktická transformace; kognitivní vývoj; učebnice; modal verbs; didactic transformation; cognitive development; textbook